Basically in Singapore English. Issue 4 (11th March 2021) - Lange, Claudia
Abstract: While much has been written about the unique set of discourse particles in colloquial Singapore English, other discourse markers which belong to the common core of English have been neglected. This paper deals with basically, a rather recent addition to the paradigm of discourse markers which typically move along the following clines in their development: clause‐internal adverbial > sentence adverbial > discourse particle; scope within the proposition > scope over the proposition > scope over discourse. This paper will use the evidence from the Singaporean subcorpus of the International Corpus of English (ICE) to trace the functions and contexts for basically and to determine whether the grammaticalization clines proposed on the basis of British English also hold for an Outer Circle variety such as Singapore English with its rich array of indigenized discourse particles.